Endoscopic management of biliary fascioliasis and identification of fasciola fluke based on mitochondrial DNA: A case report from Thailand - Pongsri Tippawangkosol (2018)
© 2017, SEAMEO TROPMED Network. All rights reserved. A patient from western Thailand with biliary fascioliasis was admitted at Maharaj Nakorn Chiang Mai Hospital, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand. The patient presented with right-upper-quadrant abdominal pain with no history of jaundice. Laboratory results showed eosino-philia. Ultrasonography and computerized tomography revealed biliary dilation in the intrahepatic and extrahepatic bile ducts, with duct wall thickening, but these observations did not help clarify the differential diagnosis. Endoscopic retrograde cholangiopancreatography (ERCP) showed dilatation of the common bile duct caused by obstruction from a fluke. After removal of the fluke and treating with triclabendazole, the symptoms disappeared and the laboratory values returned to normal. Morphological identification of fresh and carmine-stained fluke and DNA sequencing of mitochondrial cytochrome c oxidase subunit I gene identified the fluke as Fasciola gigantica. This report endorses the diagnostic and therapeutic role of ERCP in patients who present with right-upper-quadrant pain without jaundice caused by fascioliasis.